<span> 2(2x-3y=3)..................4x-6y=6..........equation 1
3(5x+2y=17)
...........15x+6y=51</span>........equation 2
adding equation 1 and equation 2;
19x=57
x=3
2x-3y=3
(2*3)-3y=3
6-3=3y
y=1
Answer:
28 x^3
Step-by-step explanation:
4x(7x^2)
4 * x* 7* x*x
4*7 x*x*x
28 x^3
Answer:
1/8
Step-by-step explanation:
To simplify the expression √3/√8, we can first simplify the square root terms by finding the prime factorization of each number under the square root. The prime factorization of 3 is 3, and the prime factorization of 8 is 2 * 2 * 2.
We can then rewrite the square root terms as follows:
√3/√8 = √(3) / √(2 * 2 * 2)
Next, we can use the property of square roots that says that the square root of a number is equal to the square root of each of its prime factors. This means that we can rewrite the square root term as follows:
√(3) / √(2 * 2 * 2) = √(3) / √(2) / √(2) / √(2)
Since the square root of a number is the same as the number itself, we can simplify the expression further by removing the square root symbols from the prime numbers 2:
√(3) / √(2) / √(2) / √(2) = √(3) / 2 / 2 / 2
Finally, we can use the rules of division to simplify the expression even further:
√(3) / 2 / 2 / 2 = √(3) / (2 * 2 * 2)
Since any number divided by itself is equal to 1, we can simplify the expression one last time to get our final answer:
√(3) / (2 * 2 * 2) = 1/2 * 1/2 * 1/2 = 1/8
Therefore, the simplified form of the expression √3/√8 is 1/8.
Answer:
1 solution
Step-by-step explanation: